Comparative assessment of butterfly species in Durgapur city: a case study - Sanchari Sarkar; Rohit Shaw; Moitreyee Chakrabarty (The Holistic Approach to Environment)
Butterflies, as charismatic and colourful insects, play a vital role in ecosystem health and serve as bio-indicators. In the context of Durgapur, West Bengal, India, a study was conducted to investigate the monthly diversity of butterflies in three different habitat types. These sites included dense vegetation with closed canopy cover, forest edges, and areas affected by human intervention. From November 2021 to May 2022, a total of 39 species of butterflies belonging to four families were recorded: Papilionidae, Pieridae, Nymphalidae, and Lycaenidae. The Nymphalidae family dominated with 44 % of observed species. The highest diversity and abundance were found in forest edge areas, while dense forests and human-influenced habitats showed lower butterfly diversity. The survival of these fragile, but necessary insects can be ensured if their ecological responsibilities are understood, and their diverse habitats preserved.